2015
DOI: 10.1021/acs.jpclett.5b00569
|View full text |Cite
|
Sign up to set email alerts
|

How Morphology Affects Singlet Fission in Crystalline Tetracene

Abstract: The dependence of exciton dynamics on the crystalline morphology of tetracene is investigated using time-resolved photoluminescence. Single crystals exhibit relatively slow singlet decays with times that range from 130 to 300 ps depending on the sample. This decay has an activation energy of ∼450 cm(-1) over the temperature range of 200-400 K. Single-crystal samples also exhibit more pronounced quantum beats due to the triplet pair spin coherences. Polycrystalline thin films grown by thermal evaporation have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
214
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(237 citation statements)
references
References 52 publications
19
214
2
2
Order By: Relevance
“…We chose to focus on F 2 -TES ADT as, unlike tetracene, F 2 -TES ADT shows no significant structural phase transition in the thin films (Supplementary Fig. 4), no evidence of ‘excimer’ emission4344 and strong triplet features in transient absorption (TA) spectra. In dilute solution only singlet states emit, with a lifetime of 12 ns.…”
Section: Resultsmentioning
confidence: 99%
“…We chose to focus on F 2 -TES ADT as, unlike tetracene, F 2 -TES ADT shows no significant structural phase transition in the thin films (Supplementary Fig. 4), no evidence of ‘excimer’ emission4344 and strong triplet features in transient absorption (TA) spectra. In dilute solution only singlet states emit, with a lifetime of 12 ns.…”
Section: Resultsmentioning
confidence: 99%
“…104,105 Studies in amorphous films of acenes yield similar results. 106,107 The effect of defects in amorphous xSF materials is an important area for future study. Application in bulk heterojunctions or other architectures, where large single crystals cannot be employed, demand an understanding and control over such effects.…”
Section: Singlet Fission For Enhancedmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43] In this case, a largely unexplored question is the relationship between SF process and SE migration. Several experiments 37,38,40 have observed that the SE delocalization can drive a rapid SF process in well-arranged molecular crystals.…”
Section: Introductionmentioning
confidence: 99%